1975
DOI: 10.1073/pnas.72.9.3453
|View full text |Cite
|
Sign up to set email alerts
|

Histidine regulation in Salmonella typhimurium: an activator attenuator model of gene regulation.

Abstract: An activator-attenuator model of positive control, as opposed to the classic repressor-operator model of negative control, is proposed for the major operon-specific mechanism governing expression of the histidine gene cluster of Salmonella typhimurium. Evidence for this mechanism is derived from experiments performed with a coupled in vitro transcription-translation system, as well as with a minimal in vitro transcription system [Kasai, T. (1974) The likelihood that tRNA and tRNA modifications are involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 28 publications
4
53
0
Order By: Relevance
“…Studies on the regulation of the his operon of S. typhimurium, a gene cluster that may have a similar mechanism of termination control, indicate that translation is a prerequisite for transcription (26), a situation contrary to the one we suggest for the trp operon.…”
Section: Methodsmentioning
confidence: 51%
“…Studies on the regulation of the his operon of S. typhimurium, a gene cluster that may have a similar mechanism of termination control, indicate that translation is a prerequisite for transcription (26), a situation contrary to the one we suggest for the trp operon.…”
Section: Methodsmentioning
confidence: 51%
“…With respect to the conversion of uridine into pseudouridine, we know that it always occurs (tRNAVal is probably a special case) but it is not essential for the function of tRNA as adaptor of aminoacids. HisT mutant tRNA's which lack pseudouridine in this region functions perfectly well in the aminoacylation reaction and in protein synthesis (17,18). On the other hand these mutant tRNA are unable to participate in the transcriptional regulation of several operons (10,12), suggesting that pseudouridine is important for the role of tRNA in regulation (19).…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this regulation, a variety of strategies can be used, involving different interplay between metabolites, enzymes, and regulatory proteins. In many cases involving model organisms, the regulatory framework that controls this process is known, and research over past decades has revealed a number of different regulatory strategies (1)(2)(3)(4).…”
mentioning
confidence: 99%